Philosophy of education in a new key: Publicness, social justice, and education; a South-North conversation. Issue 8 (9th June 2022) - Biesta, Gert; Heugh, Kathleen; Cervinkova, Hana; Rasiński, Lotar; Osborne, Sam; Forde, Deirdre; Wrench, Alison; Carter, Jenni; Säfström, Carl Anders; Soong, Hannah; O'Keeffe, Suzanne; Paige, Kathryn; et al.
Abstract: Public education is not just a way to organise and fund education. It is also the expression of a particular ideal about education and of a particular way to conceive of the relationship between education and society. The ideal of public education sees education as an important dimension of the common good and as an important institution in securing the common good. The common good is never what individuals or particular groups want or desire, but always reaches beyond such particular desires towards that which societies as a whole should consider as desirable. This does, of course, put the common good in tension with the desires of individuals and groups. Neo-liberal modes of governance have, over the past decades, put this particular educational set up under pressure and have, according to some, eroded the very idea of the common good. This set of contributions reflects on this state of affairs, partly through an exploration of the idea of publicness itself – how it can be rearticulated and regained – and partly through reflections on the current state of education in the 'north' and the 'south.'